Comparison of Micro-Percutaneous and Mini-Percutaneous Nephrolithotomy in the Treatment of Renal Stones: A Systematic Review and Meta-Analysis - Gao, Xiaoshuai; Wang, Wei; Peng, Liao; Di, Xingpeng; Xiao, Kaiwen; Chen, Jixiang; Jin, Tao (Frontiers in Surgery, 2021)
Background: To assess the efficacy and safety of micropercutaneous nephrolithotomy (Microperc) and mini-percutaneous nephrolithotomy (Miniperc) for moderately sized renal stones. Methods: Literature search of PubMed, Web of Science, and Embase was performed before January 2021. We used odds ratios (OR) and weighted mean difference (WMD) for dichotomous variables and continuous variables, respectively. Results were pooled by Review Manager version 5.3 software. Results: A total of 6 studies involving 291 Microperc and 328 Miniperc cases were included. The overall SFR of Microperc was 87.29% (254/291), while the SFR of the Miniperc was 86.59% (284/328). Microperc was associated with lower hemoglobin drop (WMD: -0.98; P = 0.03), higher renal colic requiring D-J stent insertion (OR: 3.49; P=0.01). No significant differences exist between Microperc and Miniperc with respect to stone-free rate (SFR) (OR: 1.10; P=0.69), urinary tract infection (OR: 0.38; P=0.18), operative time (WMD: -5.76; P = 0.62) and hospital stay time (WMD: -1.04; P=0.07). Conclusions: Our meta-analysis demonstrated that Microperc could obtain comparable SFR with Miniperc. Microperc was associated with lower hemoglobin drop, but Miniperc was associated with lower renal colic rates. In addition, the operation time and hospital stay time for these two procedures were similar.